The Effectiveness of Ezzlemath for Improving the Reading Comprehension of Mathematics Problems at Grade Five of ICP Elementary School - Ima Kulama Gutami; Adelia Nathasyach; Oktavia Dwi Widianti; Chyntia Heru Woro Prastiwi (Jurnal Pendidikan Edutama, 2022)
Mathematic problems often become obstacles to the students of ICP (International Class Program) schools in Indonesia, including the elementary school level. They cannot understand sentences presented in mathematic problems because they have constraints in the mathematical vocabulary. To overcome this problem, this research under the experimental design conducted experiments on using Ezzlemath (English Puzzle for Mathematics) for assisting the students’ reading comprehension upon mathematic problems. By having fun in doing a puzzle and repeated words filled in the puzzle, the students of elementary school level of ICP design can have more exposure to mathematical vocabulary. The researchers involved 12 students of grade 5A as the experimental group and 17 students of grade 5B as the control group. The research results demonstrated that Ezzlemath gave significant effects to the students’ reading comprehension of mathematic problems.   Soal cerita Matematika sering menjadi kendala bagi siswa-siswi di sekolah-sekolah berdesign ICP (Internasional Class Program atau Program Kelas Internasional), termasuk pada level Sekolah Dasar (SD). Siswa-siswi tidak bisa memahami soal cerita Matematika karena mereka memiliki keterbatasan kosakata istilah-istilah Matematika dalam Bahasa Inggris. Untuk mengatasi masalah ini, penelitian eksperimental ini menerapkan Ezzlemath (English Puzzle for mathematics atau Puzzle Matematika Berbahasa Inggris) untuk mempermudah pemahaman bacaan terhadap soal cerita Matematika. Dengan mengerjakan puzzle teka teki silang secara menyenangkan dan mengulang kata-kata dalam puzzle, maka siswa-siswi SD sekolah berdesign ICP dapat mengalami banyak exposure terhadap istilah Matematika berbahasa Inggris. Para peneliti melibatkan 12 murid kelas 5A sebagai kelas eksperimental dan 17 murid kelas 5B sebagai kelas kontrol. Hasil penelitian mengindikasikan bahwa Ezzlemath mampu memberikan efek signifikan terhadap kemampuan pemahaman bacaan siswa terhadap soal cerita Matematika berbahasa Inggris.